Peran Kolaboratif Pendidik Dan Tenaga Kependidikan Dalam Meningkatkan Efektivitas Pembelajaran Di SMP 13 Medan - Nainggolan, Martina Agnes Octavia; Cindy Clara Siregar; Ruth Masta Yemima Sibarani; Roria Natal Simbolon; Windry Sary Sihombing (CV. ITTC INDONESIA, 2026)
This study aims to analyze the collaborative role between educators and administrative staff in improving the effectiveness of learning at SMP 13 Medan. The method used is descriptive qualitative through semi-structured interviews. The results of the study indicate that collaboration between teachers and administrative staff has been running well through harmonious communication, clear division of tasks, and optimal administrative and technical support. Teachers focus on pedagogical aspects, while educational staff support the smooth operation of learning, including the provision of student data and infrastructure. This synergy is able to improve work efficiency, enrich learning resources, and create a more structured and oriented learning to the needs of students. In addition, coordination through work meetings also strengthens the alignment of educational goals. Thus, collaboration between educators and educational staff is a strategic factor in improving the quality and effectiveness of learning in schools.